Ar-Matrix Studies of the Photochemical Reaction between CS2and ClF: Prereactive Complexes and Bond Isomerism ofthe Photoproducts - Custodio Castro, Michelle Tatiana (2022)
In this work, prereactive complexes, reaction products, and conformational preferencesderived from the photochemical reaction between CS2and ClF were analyzed following the code-position of the reactants trapped in argon matrices at cryogenic temperatures. After codepositionof CS2and ClF diluted in Ar, the formation of van der Waals complexes is observed. When themixture is subsequently irradiated by means of broad-band UV-visible light (225≤λ≤800 nm),fluorothiocarbonylsulfenyl chloride (FC(S)SCl) and chlorothiocarbonylsulfenyl fluoride (ClC(S)SF)are produced. These species exist as two stable planar anti- and syn-conformers (anti- and syn- of theC=S double bond with respect to the S–Cl or S–F single bond, respectively). For both novel molecules,anti-FC(S)SCl and anti-ClC(S)SF are the lowest-energy computed rotamers. As expected due to thephotochemical activity of these species, additional reaction products due to alternative or subsequentphotochannels are formed during this process.